Determinants of muslims teachers' practice on infusing islamic manners(Adab) in the classroom in the three southern boarder provinces - Sa-U, Samsoo; Mohd Ali, Hairuddin; Nordin, Mohamad Sahari; Ssekamanya, Siraje Abdallah; Syed Hassan, Sharifah Sariah (2010)
The objectives of this research are to develop, examine and validate a model of infusing Islamic manners (adab) in the classroom (iMIS). A proposed model consists of endogenous variables (teacher attributes and perceived support) and exogenous variables (teachers‟ performance in iMIS). A survey instrument was administratered to 371 Malay-Muslim teachers at public primary schools in Narathiwat, Yala and Pattani Provinces,Thailand. The structural equation modeling (SEM) is used to validate and test the model fit to the empirical data. The results show that the only three proposed teacher attributes (self-efficacy, values and organizational commitment) and two factors of teachers‟ perceived support (peer and curriculum support) directly influence to their performance in iMIS. Discussion centers the practical implications of these results.